Patent Law's Functionality Malfunction and the Problem of Overbroad, Functional Software Patents - Kevin Emerson Collins (Washington University Law Review, 2013)
Contemporary software patents are problematic because they are often overbroad. This Article offers a novel explanation of the root cause of this overbreadth. Patent law suffers from a functionality malfunction: the conventional scope-curtailing doctrines of patent law break down and lose their ability to rein in overbroad claims whenever they are brought to bear on technologies, like software, in which inventions are purely functional entities. In addition to identifying the functionality malfunction in the software arts, this Article evaluates the merits of the most promising way of fixing it. Courts can identify algorithms as the metaphorical structure of software inventions and limit claim scope to particular algorithms for achieving a claimed function. However, framing algorithms as the metaphorical structure of software inventions cannot put the scope of software patents on par with the scope of patents in other arts. Most importantly, the recursive nature of algorithms and Gottschalk v. Benson create to-date unappreciated problems.
Keywords: software patents; functionality; patent law; algorithms; Gottschalk v. Benson